Analisis Pemasaran Kelapa Dalam di Kabupaten Tabanan - FRANSISKA, PUTU IKA; SUSRUSA, KETUT BUDI; ANGGRENI, I.G.A.A LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Marketing Analysis of Dalam Coconut in Tabanan Regency This study aims to determine the marketing channels for Dalam Variety Coconut commodity in Tabanan Regency, from farmers to producers to consumers (but limited to collector traders). Marketing functions, institutions, and the level of marketing efficiency are identified by analyzing marketing margins, farmer's share as well as profit and cost ratios. Descriptive qualitative analysis is used to analyze marketing channels, functions and marketing institutions. Quantitative analysis is used to analyze marketing efficiency. Respondents of this study were 15 farmers and 23 representatives of marketing institutions.         The results show that there are two marketing channels, namely: (1) farmers - middlemen traders - collector traders, and (2) farmers - collector traders. Both marketing channels are efficient when viewed from the percentage of farmer's share which is more than 40%. The marketing margin in marketing channel I is Rp. 1,083.25, while in marketing channel II it is Rp. 800. The level of efficiency of a marketing system can also be seen from the ratio of profits and costs incurred by all marketing agencies. The profit and cost ratio value for marketing channel I is 2.87 per item, while in marketing channel II is 3.35 per item. Each marketing agency performs three main functions, namely a physical function, an exchange function and a facility function. Producer farmers perform exchange functions, facility functions and sometimes also perform physical functions, such as transport.